Авторське право на комп’ютерну програму - Леушина, А. А.; Олейнікова, О. І. (ХНУРЕ, 2022)
This report examines the terms and object of copyright. Inform about an efficient way of protecting a computer program. The theses is exploring benefits of intellectual property protection